EVALUATION OF THE EFFECTIVENESS OF THE IMPLEMENTATION OF SERVICE STANDARD POLICIES ON SERVICE QUALITY IN THE CALIBRATION LABORATORY OF THE TESTING AND TESTING UPT MEDAN GOODS QUALITY CERTIFICATION - Eka Farra Dewi Sitompul; Sukaria Sinulingga; Fadli; Sugih Arto; Syafrizal Helmi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims Optimal and excellent public service, the expectation of all citizens, serves as a benchmark for the performance of public service institutions/agencies. Describing public dissatisfaction with public services will consistently inform government improvements in evaluating implemented policies To achieve these goals, good, high-quality service is required.Because good, quality service can help the government achieve these goals. Service is crucial for every citizen, as the better the quality of service provided, the greater the public's trust in the government operating in that service sector. Service standards are benchmarks used as guidelines for service delivery and as a reference for assessing service quality as an obligation and promise of service providers to the public in the context of providing quality, fast, easy, affordable, and orderly services. , a hypothesis is a temporary answer to a research problem, where the problem statement can be a statement about the relationship between two or more variables, comparisons, or independent variables